Structural Response Analysis During Slamming Events on Speedboats Using Aluminum Material - Wulandari, Amalia Ika; Syahab, Husein; Baidowi, Achmad; Adietya, Berlian Arswendo (International Journal of Marine Engineering Innovation and Research, 2025)
The structural response analysis of an aluminum speedboat during slam-ming due to regular waves was conducted using the one-way fluid-structure interaction method. This method involves generating waves through hydrody-namic diffraction to obtain loads, which are then applied to the ship's struc-ture and analyzed using finite element analysis. It is known that the greater the force generated from slamming , the stress and deformation at the critical load point will increase. In addition to being influenced by the critical point, the maximum stress is also influenced by the ship's construction design. It has been found that the highest stress and deformation occur on the surface of the plate that is not supported by the transverse construction. Therefore, it can be concluded that the construction design can influence the magnitude of the structural response to the slamming event . Efforts that can be made by ship designers and manufacturers are to convert ships by using materials that are better at absorbing loads, such as the use of sandwich materials